Entamoeba histolytica Dmc1 Catalyzes Homologous DNA Pairing and Strand Exchange That Is Stimulated by Calcium and Hop2-Mnd1 - Kelso, Andrew A.; Say, Amanda F.; Sharma, Deepti; Ledford, LeAnna L.; Turchick, Audrey; Saski, Christopher A.; King, Ada V.; Attaway, Christopher C.; Temesvari, Lesly A.; Sehorn, Michael G. (PLOS ONE, 2015)
Meiosis depends on homologous recombination (HR) in most sexually reproducing organisms. Efficient meiotic HR requires the activity of the meiosis-specific recombinase, Dmc1. Previous work shows Dmc1 is expressed in Entamoeba histolytica, a eukaryotic parasite responsible for amoebiasis throughout the world, suggesting this organism undergoes meiosis. Here, we demonstrate Dmc1 protein is expressed in E. histolytica. We show that purified ehDmc1 forms presynaptic filaments and catalyzes ATP-dependent homologous DNA pairing and DNA strand exchange over at least several thousand base pairs. The DNA pairing and strand exchange activities are enhanced by the presence of calcium and the meiosis-specific recombination accessory factor, Hop2-Mnd1. In combination, calcium and Hop2-Mnd1 dramatically increase the rate of DNA strand exchange activity of ehDmc1. The biochemical system described herein provides a basis on which to better understand the role of ehDmc1 and other HR proteins in E. histolytica.